Nano detection material for detecting heavy metal ions in industrial sewage and preparation method of nano detection material

By functionally modifying the surface of gold nanoparticles and introducing imidazole groups and disulfide bonds, the low concentration and complex environmental problems of heavy metal ions detection in industrial wastewater are solved, and the detection effect of high sensitivity and stability is achieved.

CN119609150AActive Publication Date: 2025-03-14NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510149946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

When detecting heavy metal ions in industrial wastewater, the prior art faces the problems of low concentration detection difficulty and complex pollution of the environment, resulting in insufficient detection sensitivity and stability.

Method used

By functionalizing the surface modification of the gold nanoparticles, modified cellulose modified from imidazole groups is introduced to the surface of the gold nanoparticles, and disulfide bonds are introduced to the modified cellulose, thereby stabilizing the gold nanoparticles through the affinity of sulfur elements and gold, improving their stability and detection performance in different environments.

Benefits of technology

It realizes the maintenance of detection stability and sensitivity in different environments, improves the selectivity and detection limit for heavy metal ions, and enhances the multi-environmental adaptability of nanodetection materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609150A_ABST
    Figure CN119609150A_ABST
Patent Text Reader

Abstract

The invention discloses a nano detection material for detecting heavy metal ions in industrial sewage and a preparation method of the nano detection material, and belongs to the technical field of detection materials. Gold nanoparticles are subjected to functional surface modification, modified cellulose modified by imidazole groups is introduced to the surfaces of the gold nanoparticles, disulfide bonds are introduced to the modified cellulose, and the nano detection material is prepared. Therefore, the gold nanoparticles are stabilized through the affinity of the sulfur element and gold, the stability of the gold nanoparticles in different environments is improved, and the detection stability and sensitivity in different environments are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of detection materials, and specifically refers to a nanometer detection material for detecting heavy metal ions in industrial sewage and a preparation method thereof. Background Art

[0002] Heavy metal pollution in industrial wastewater refers to the presence of excessive heavy metal elements in wastewater discharged during industrial production, such as lead (Pb), cadmium (Cd), mercury (Hg), chromium (Cr), copper (Cu), etc. Heavy metals cannot be naturally degraded and will accumulate in water bodies, soil and organisms, causing long-term ecological environmental pollution and serious health hazards; industrial wastewater has a wide range of sources, for example: in the metallurgical industry, during the process of smelting metals, wastewater and waste gas containing heavy metals such as lead, cadmium, chromium, copper, and zinc are often produced. These heavy metals will not only be discharged during the smelting process, but may also be released in the corrosion of production equipment, furnaces and other equipment; in the electroplating industry, heavy metals used in the electroplating process, such as chromium, nickel, zinc, etc., will cause serious pollution after being discharged into the wastewater; in the chemical industry, heavy metals used and discharged in the production of fertilizers, pesticides, dyes and other chemical products; in the battery manufacturing industry, nickel-cadmium batteries Heavy metals such as lead, cadmium and mercury are emitted during the production of lithium-ion batteries, etc.; in electronic waste treatment: improper handling of electronic waste may lead to the release of heavy metals such as lead, mercury and copper; in the leather and textile industry: during the leather tanning and dyeing process, metal ions such as chromium, copper and zinc may be emitted; heavy metal ions have biological toxicity and cumulative effects, which directly affect the aquatic ecosystem and human health: after entering the water body, heavy metal ions are transmitted step by step through the food chain of aquatic plants and animals, eventually leading to ecological imbalance. They can interfere with the normal physiological activities of organisms, such as causing reproduction difficulties, growth stagnation and even death of aquatic organisms; through the food chain or directly drinking contaminated water, heavy metals enter the human body and accumulate in the body, causing chronic poisoning. For example, lead can damage the nervous system, mercury can cause renal failure, and cadmium can cause bone softening and kidney disease. Long-term exposure may cause serious diseases such as cancer.

[0003] Although existing technologies are capable of detecting and treating heavy metal ions in industrial wastewater, they still face many challenges: Low-concentration detection: Some heavy metal ions are still biologically toxic at extremely low concentrations, so the sensitivity of detection technology needs to be further improved; Complex polluted environment: Industrial wastewater has a complex composition and may contain a variety of heavy metals and organic pollutants, which makes detection and treatment more difficult. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a nano detection material for detecting heavy metal ions in industrial wastewater and a preparation method thereof. The present invention functionalizes the surface of gold nanoparticles, introduces modified cellulose modified by imidazole groups into the surface of the gold nanoparticles, and introduces disulfide bonds into the modified cellulose, thereby stabilizing the gold nanoparticles through the affinity of sulfur element and gold, improving the stability of the gold nanoparticles in different environments, and ensuring the detection stability and sensitivity in different environments.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a nanometer detection material for heavy metal ion detection in industrial wastewater, which specifically comprises the following steps:

[0006] S1. Disperse cellulose in a 50 vol% methanol aqueous solution, adjust the pH to 4-4.5, place in a nitrogen environment, add AIBN and mix well to obtain a pretreated cellulose solution;

[0007] S2, dissolving N-hydroxyethyl acrylamide in DMF, adding imidazole-2-carboxylic acid methyl ester, mixing at a speed of 150-180 rpm, adding p-toluenesulfonic acid, raising the reaction temperature to 120-140° C., and performing reflux reaction for 5-7 hours. After the reaction is completed, adding deionized water for washing until the reaction system is neutral, distilling under reduced pressure, and freeze-drying to obtain imidazolyl acrylamide;

[0008] S3, adding the imidazolyl acrylamide solution to the pretreated cellulose solution prepared in step S2, mixing evenly, adding N,N'-bis(acryloyl)cystamine, placing under nitrogen conditions, raising the reaction temperature to 60-80°C, stirring at a speed of 200-250 rpm, reacting for 4-6 hours, washing with anhydrous ethanol, and vacuum drying to obtain modified cellulose;

[0009] S4, dissolving the modified cellulose prepared in step S3 in DMAC, preparing a HAuCl4 solution and dropping it into the reaction system, stirring and reacting for 30-40 minutes, adding a NaBH4 aqueous solution to ice water, continuing to stir and react for 15-25 minutes, washing with deionized water, and vacuum drying to obtain a nano detection material;

[0010] Preferably, in step S1, the mass fraction of cellulose in the methanol aqueous solution is 3%-5%;

[0011] Preferably, in step S1, the mass ratio between AIBN and cellulose is 1:8-10;

[0012] Preferably, in step S2, the mass concentration of N-hydroxyethyl acrylamide in dichloromethane is 40-50 g / L;

[0013] Preferably, in step S2, the mass ratio between the N-hydroxyethyl acrylamide and the imidazole-2-carboxylic acid methyl ester is 1:1.1-1.2;

[0014] Preferably, in step S2, the added mass of p-toluenesulfonic acid is 10%-12% of the mass of N-hydroxyethyl acrylamide;

[0015] Preferably, in step S3, the imidazolyl acrylamide solution is a solution of imidazolyl acrylamide dissolved in a methanol aqueous solution, wherein the mass concentration of imidazolyl acrylamide is 40-80 g / L, and the volume fraction of methanol in the methanol aqueous solution is 60%-80%;

[0016] Preferably, in step S3, the mass ratio between the imidazolyl acrylamide and the cellulose is 1:1.25-1.5;

[0017] Preferably, in step S3, the added mass of the N,N'-bis(acryloyl)cystamine is 10%-20% of the mass of imidazolyl acrylamide;

[0018] Preferably, in step S4, the mass fraction of the modified cellulose in DMAC is 1%-4%;

[0019] Preferably, in step S4, in the HAuCl4 solution, the mass concentration of HAuCl4 in DMAC is 4-5 g / L; the added mass of HAuCl4 is 3.6%-5% of the mass of the modified cellulose;

[0020] Preferably, in step S4, the mass concentration of NaBH4 in the NaBH4 solution is 10-12 g / L; the added mass of NaBH4 is 4%-6% of the mass of the modified cellulose.

[0021] The present invention also provides a nanometer detection material for detecting heavy metal ions in industrial wastewater, which is prepared according to the above preparation method.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The invention provides a nanometer detection material for detecting heavy metal ions in industrial sewage and a preparation method thereof. The invention performs functional surface modification on gold nanometer particles, introduces modified cellulose modified by imidazole groups to the surface of the gold nanometer particles, and introduces disulfide bonds to the modified cellulose, thereby stabilizing the gold nanometer particles by the affinity between sulfur elements and gold, improving the stability of the gold nanometer particles in different environments, and ensuring the detection stability and sensitivity in different environments. The invention grafts imidazole groups on acrylamide, uses bisacrylamide with disulfide bonds as a crosslinking agent, and modifies the cellulose. The affinity between sulfur elements in the disulfide bonds and gold ions is used to improve the binding performance of S and Au, synthesizes the gold nanometer particles in situ, and after the reaction is completed, washes with deionized water to neutrality to prepare the heavy metal ion nanometer detection material. The invention introduces imidazole groups and SS bonds to the gold nanometer particles, and can avoid the influence of protonation on the surface performance of the gold nanometer particles by the imidazole groups under acidic conditions, thereby maintaining the detection performance of the gold nanometer particles, and can expose S by breaking the SS bonds under alkaline conditions. - Avoid excessive aggregation of cations in gold nanoparticles, which affects the detection performance, thereby improving the stability of nano-detection materials in various environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The nanometer detection material prepared in Example 1 is used to detect Hg at different concentrations. 2+ UV-vis images;

[0025] Figure 2 This is a graph showing the selectivity of the nanometer detection material prepared in Example 1 of the present invention to heavy metal ions;

[0026] Figure 3 The sensitivity result diagram of the nanometer detection materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0027] Figure 4 The graph is a graph showing the stability results of the nanometer detection materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 at different pH values.

[0028] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0031] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.

[0032] Example 1

[0033] This embodiment provides a method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater, which specifically includes the following steps:

[0034] S1. Accurately weigh 5 g of cellulose and place it in a flask. Add 100 mL of 50 vol% methanol aqueous solution in portions, stir thoroughly at 150 rpm until the cellulose is evenly dispersed, adjust the pH to 4.5, accurately weigh 0.5 g of AIBN, introduce nitrogen to replace the oxygen in the reaction system, and continue stirring until the reaction system is uniform to obtain a pretreated cellulose solution;

[0035] S2. Accurately weigh 3 g of N-hydroxyethyl acrylamide and place it in a new flask, add 75 mL of DMF solvent, place it on a magnetic stirrer and stir at a speed of 120 rpm. After the N-hydroxyethyl acrylamide is completely dissolved, add 3.3 g of imidazole-2-carboxylic acid methyl ester to the reaction system, adjust the speed to 180 rpm for thorough mixing, add 0.3 g of p-toluenesulfonic acid, increase the reaction temperature to 140° C., perform reflux reaction for 5 hours, wait for the reaction system to cool to room temperature, wash the reaction system with deionized water until it is neutral, perform vacuum distillation, remove the reaction solvent, and then freeze-dry to obtain imidazolyl acrylamide;

[0036] S3, accurately weigh 4g of imidazole acrylamide prepared in step S2, dissolve it in 50mL80vol% methanol aqueous solution, add it to the pretreated cellulose solution prepared in step S2, place it on a magnetic stirrer and stir it at a speed of 150rpm, after mixing evenly, add 0.4g of N,N'-bis(acryloyl)cystamine, introduce nitrogen into the reaction system, continue mixing, increase the reaction temperature to 70°C, set the stirring speed to 250rpm, react for 5h, wait for the reaction system to cool to room temperature, add 500mL of anhydrous ethanol for washing, place it at 5000rpm for centrifugation for 5min, remove the supernatant, and wash the lower layer of reactants with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 30°C for 15h to obtain modified cellulose;

[0037] S4. Accurately weigh 1.0 g of the modified cellulose prepared in step S3 and place it in a flask. Add 100 mL of DMAC and mix at a speed of 200 rpm to fully disperse the modified cellulose in DMAC. Accurately weigh 4.0 g of HAuCl4 and dissolve it in 10 mL of deionized water. After mixing evenly, take 1 mL of it and dilute it with 10 mL of DMAC. After the solution is mixed evenly, take 9 mL and add it dropwise to the reaction system at a speed of 1 mL / min. Stir at a speed of 200 rpm for 40 min. Transfer the reaction system to an ice-water bath. Accurately weigh 0.1 g of NaBH4 and place it in a volumetric flask and make up the volume with 10 mL of deionized water. After the reaction system is cooled, add 4 mL of NaBH4 solution dropwise to the reaction system at a speed of 0.5 mL / min. After the addition is complete, continue to stir the reaction for 20 min. After the reaction is completed, wash with deionized water until there is no chloride ion in the product, and place it at 50°C and vacuum dry for 12 h to obtain a nano detection material.

[0038] This embodiment also provides a nanometer detection material for detecting heavy metal ions in industrial wastewater, which is prepared according to the above preparation method.

[0039] Example 2

[0040] This embodiment provides a method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater, which specifically includes the following steps:

[0041] S1. Accurately weigh 3 g of cellulose and place it in a flask. Add 100 mL of 50 vol% methanol aqueous solution in portions, stir thoroughly at 150 rpm until the cellulose is evenly dispersed, adjust the pH to 4, accurately weigh 0.35 g of AIBN, introduce nitrogen to replace the oxygen in the reaction system, and continue stirring until the reaction system is uniform to obtain a pretreated cellulose solution;

[0042] S2. Accurately weigh 5 g of N-hydroxyethyl acrylamide and place it in a new flask, add 100 mL of DMF solvent, place it on a magnetic stirrer and stir at a speed of 120 rpm. After the N-hydroxyethyl acrylamide is completely dissolved, add 6 g of imidazole-2-carboxylic acid methyl ester to the reaction system, adjust the speed to 150 rpm for thorough mixing, add 0.6 g of p-toluenesulfonic acid, increase the reaction temperature to 120° C., perform reflux reaction for 7 hours, wait for the reaction system to cool to room temperature, wash the reaction system with deionized water until it is neutral, perform vacuum distillation, remove the reaction solvent, and then freeze-dry to obtain imidazolyl acrylamide;

[0043] S3, accurately weigh 2g of imidazolyl acrylamide prepared in step S2, dissolve it in 50mL70vol% methanol aqueous solution, add it to the pretreated cellulose solution prepared in step S2, place it on a magnetic stirrer and stir it at a speed of 150rpm, after mixing evenly, add 0.3g of N,N'-bis(acryloyl)cystamine, introduce nitrogen into the reaction system, continue mixing, increase the reaction temperature to 80°C, set the stirring speed to 200rpm, react for 6h, wait for the reaction system to cool to room temperature, add 500mL of anhydrous ethanol for washing, place it at 5000rpm for centrifugation for 5min, remove the supernatant, and wash the lower layer of reactants with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 30°C for 15h to obtain modified cellulose;

[0044] S4. Accurately weigh 1.0 g of the modified cellulose prepared in step S3 and place it in a flask. Add 25 mL of DMAC and mix at a speed of 200 rpm to fully disperse the modified cellulose in DMAC. Accurately weigh 5.0 g of HAuCl4 and dissolve it in 10 mL of deionized water. After mixing evenly, take 1 mL of it and dilute it with 10 mL of DMAC. After the solution is mixed evenly, add it dropwise to the reaction system at a speed of 1 mL / min. Stir at a speed of 200 rpm for 40 min. Transfer the reaction system to an ice-water bath. Accurately weigh 0.1 g of NaBH4 and place it in a volumetric flask and make up to volume with 10 mL of deionized water. After the reaction system is cooled, add 6 mL of NaBH4 solution to the reaction system at a speed of 0.5 mL / min. After the addition is complete, continue to stir the reaction for 15 min. After the reaction is completed, wash with deionized water until there is no chloride ion in the product, and place it at 50°C and vacuum dry for 12 h to obtain a nano detection material.

[0045] This embodiment also provides a nanometer detection material for detecting heavy metal ions in industrial wastewater, which is prepared according to the above preparation method.

[0046] Example 3

[0047] This embodiment provides a method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater, which specifically includes the following steps:

[0048] S1. Accurately weigh 4 g of cellulose and place it in a flask. Add 100 mL of 50 vol% methanol aqueous solution in portions, stir thoroughly at 150 rpm until the cellulose is evenly dispersed, adjust the pH to 4.3, accurately weigh 0.45 g of AIBN, introduce nitrogen to replace the oxygen in the reaction system, and continue stirring until the reaction system is uniform to obtain a pretreated cellulose solution;

[0049] S2. Accurately weigh 4.5 g of N-hydroxyethyl acrylamide and place it in a new flask, add 100 mL of DMF solvent, place it on a magnetic stirrer and stir it at a speed of 120 rpm. After the N-hydroxyethyl acrylamide is completely dissolved, add 5 g of imidazole-2-carboxylic acid methyl ester to the reaction system, adjust the speed to 150 rpm for thorough mixing, add 0.5 g of p-toluenesulfonic acid, increase the reaction temperature to 130° C., perform reflux reaction for 6 hours, wait for the reaction system to cool to room temperature, wash the reaction system with deionized water until it is neutral, perform vacuum distillation, remove the reaction solvent, and then freeze-dry to obtain imidazolyl acrylamide;

[0050] S3, accurately weigh 3g of imidazole acrylamide prepared in step S2, dissolve it in 50mL60vol% methanol aqueous solution, add it to the pretreated cellulose solution prepared in step S2, place it on a magnetic stirrer and stir it at a speed of 150rpm, after mixing evenly, add 0.45g of N,N'-bis(acryloyl)cystamine, introduce nitrogen into the reaction system, continue mixing, increase the reaction temperature to 60°C, set the stirring speed to 220rpm, react for 4h, wait for the reaction system to cool to room temperature, add 500mL of anhydrous ethanol for washing, place it at 5000rpm for centrifugation for 5min, remove the supernatant, and wash the lower layer of reactants with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 30°C for 15h to obtain modified cellulose;

[0051] S4. Accurately weigh 1.0 g of the modified cellulose prepared in step S3 and place it in a flask, add 50 mL of DMAC, mix at a speed of 200 rpm, and fully disperse the modified cellulose in DMAC. Accurately weigh 4.0 g of HAuCl4 and dissolve it in 10 mL of deionized water. After mixing evenly, take 1 mL of it and dilute it with 10 mL of DMAC. After the solution is mixed evenly, add it dropwise to the reaction system at a speed of 1 mL / min, stir at a speed of 200 rpm for 35 min, transfer the reaction system to an ice-water bath, accurately weigh 0.1 g of NaBH4 and place it in a volumetric flask and make up to volume with 10 mL of deionized water. After the reaction system is cooled, 5 mL of NaBH4 solution is added dropwise to the reaction system at a speed of 0.5 mL / min. After the addition is complete, continue to stir the reaction for 25 min. After the reaction is completed, wash with deionized water until there is no chloride ion in the product, and place it at 50°C and vacuum dry for 12 h to obtain a nano detection material.

[0052] This embodiment also provides a nanometer detection material for detecting heavy metal ions in industrial wastewater, which is prepared according to the above preparation method.

[0053] Comparative Example 1

[0054] This comparative example provides a heavy metal ion nano detection material and a preparation method thereof, which differs from Example 1 only in that the preparation method does not include step S2, and in step S3, the imidazolyl acrylamide is replaced by N-hydroxyethyl acrylamide in the same mass ratio, and the components and component contents are the same as those in Example 1.

[0055] Comparative Example 2

[0056] This comparative example provides a heavy metal ion nano-detection material and a preparation method thereof, which differs from Example 1 only in that, in the preparation method, in step S3, N,N'-vinylbisacrylamide is used to replace N,N'-bis(acryloyl)cystamine in the same mass ratio, and its components and component contents are the same as those in Example 1.

[0057] Experimental Example 1

[0058] This experimental example measured the detection selectivity of the heavy metal ion nanometer detection material prepared in Example 1. -5 mol / L heavy metal ion solution, including Na + , K + Mg 2+ , Sr 2+ 、Al 3+ , Mn 2+ 、Co 2+ , Pb 2+ , Fe 2+ , Fe 3+ Cr 3+ , prepare the nanometer detection material aqueous solution according to 3g / L, add 3mL of nanometer detection material aqueous solution and 1mL of 1×10 -5 mol / L Hg 2+ solution and 1mL 1×10 -5 mol / L solutions of other heavy metal ions were placed on a UV-visible spectrophotometer for determination. Figure 1 The nanometer detection material prepared in Example 1 is used to detect Hg at different concentrations. 2+ UV-vis image, as shown in the figure, in Hg 2+ The concentration is 1.0×10 -6 M, nano-ions show a new absorption peak at 608nm. 2+ The concentration increased to 4.0×10 -6 M, the absorption peak at 608nm red-shifts to 650nm due to Hg 2+ The increase in concentration caused the aggregation of nano ions in the nano detection material to increase, causing the absorption peak to red shift; this example uses the absorbance ratio at 650nm and the absorbance ratio at 520nm as the standard for evaluating the concentration of heavy metal ions.650 / A 520 Value and Hg 2+ The linear relationship between the concentration of Hg 2+ Conduct quantitative analysis; Figure 2 The selectivity result diagram of the nanometer detection material prepared in Example 1 of the present invention for heavy metal ions is shown in the figure. The selectivity result diagram of the nanometer detection material prepared in Example 1 of the present invention for Hg 2+ Has higher selectivity.

[0059] Experimental Example 2

[0060] This experimental example measures the sensitivity of the nanometer detection materials prepared in Examples 1-3 and Comparative Examples 1-2, and configures Hg 2+ Solution, set Hg 2+ The solution concentration is 5.0×10 -7 mol / L、1.0×10 -6 mol / L、2.0×10 -6 mol / L、4.0×10 -6 mol / L、8.0×10 -6 mol / L、1.0×10 -5 mol / L, the nanometer detection materials prepared in Examples 1-3 and Comparative Examples 1-2 were added at 2 g / L, and the mixture was shaken on a shaker at 150 rpm for 10 min. The Hg 2+ concentration;

[0061] Figure 3 The sensitivity results of the nanometer detection materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in the figure. As shown in the figure, the detection limit of the nanometer detection materials prepared in Examples 1-3 is close to 1.0×10 -6 mol / L, the detection limit of the nanometer detection material prepared in Comparative Example 1 was 1.13×10 -5 mol / L, the detection limit of the nanometer detection material prepared in Comparative Example 2 was 4.27×10 -6 mol / L, indicating that the examples prepared by the present invention are effective in detecting Hg 2+ The detection limit of the nanometer detection material prepared in the comparative example is lower than that of the nanometer detection material prepared in the comparative example. The nanometer detection material prepared in the present invention can improve the detection limit of Hg by the imidazole group. 2+ The adsorption capacity of Hg 2+ At the same time, SS can improve the dispersion of gold nanoparticles in the detection material and the detection system, avoiding the gold nanoparticles from being affected by the environment, thereby improving the sensitivity of the nano detection material prepared by the present invention.

[0062] Experimental Example 3

[0063] This experimental example measures the stability of the nanometer detection materials prepared in Examples 1-3 and Comparative Examples 1-2, and configures 5.0×10 -6 mol / L Hg 2+ Solution, adjust Hg 2+ The pH of the solution was adjusted to 2.0, 4.0, 6.0, 8.0 and 10.0, and the nanometer detection material was placed in the Hg 2+ The solution was placed on a shaker at 150 rpm for 10 min and the A was measured and calculated using a UV-visible spectrophotometer. 650 / A 520 ;

[0064] Figure 4 The stability results of the nano-detection materials prepared by Examples 1-3 of the present invention and Comparative Examples 1-2 at different pH values ​​are shown in the figure. As shown in the figure, Examples 1-3 can maintain the detection performance in the range of pH=3~10. Under acidic conditions, the imidazole group can provide a protonation site to avoid the surface of the gold nanoparticles being affected by the protonation in the acidic environment. Although the pH reduction in the environment affects the detection performance of the nano-detection material to a certain extent, the nano-detection material prepared by the present invention can still maintain the detection performance. Compared with Comparative Example 1, in the absence of imidazole group modification, in an acidic environment, the gold nanoparticles are affected by the protonation in the environment, resulting in the interaction between the proton and the heavy metal cation. The competitive adsorption effect is generated between the gold nanoparticles, which greatly affects the detection performance of the gold nanoparticles; in an alkaline environment, the surface of the gold nanoparticles has a negative charge, which can improve the dispersion performance of the gold nanoparticles in the environment. When the alkalinity gradually increases, the gold nanoparticles can quickly adsorb excess heavy metal cations, resulting in a rapid increase in particle size, promoting the transition aggregation of the gold nanoparticles, and the absorbance increases rapidly, thereby affecting the detection performance of the gold nanoparticles. Compared with Comparative Example 2, the nano-detection material prepared by the present invention modifies the surface performance of the gold nanoparticles with imidazole groups and SS bonds. The SS bond maintains a stable structure in acidic and weakly alkaline states. As the alkalinity increases, the SS breaks, and the S generated after the breakage - It can avoid the transitional adsorption of a large number of metal cations on the surface of gold nanoparticles, thereby maintaining the stability of the detection performance of the nano-detection material.

[0065] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0066] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater, characterized in that: The specific steps include: S1. Disperse cellulose in a 50 vol% methanol aqueous solution, adjust the pH to 4-4.5, place in a nitrogen environment, add AIBN and mix well to obtain a pretreated cellulose solution; S2, dissolving N-hydroxyethyl acrylamide in DMF, adding imidazole-2-carboxylic acid methyl ester, mixing at a speed of 150-180 rpm, adding p-toluenesulfonic acid, raising the reaction temperature to 120-140° C., and performing reflux reaction for 5-7 hours. After the reaction is completed, adding deionized water for washing until the reaction system is neutral, distilling under reduced pressure, and freeze-drying to obtain imidazolyl acrylamide; S3, adding the imidazolyl acrylamide solution prepared in step S2 to the pretreated cellulose solution prepared in step S1, mixing evenly, adding N,N'-bis(acryloyl)cystamine, placing under nitrogen conditions, raising the reaction temperature to 60-80°C, stirring at 200-250rpm, reacting for 4-6h, washing with anhydrous ethanol, and vacuum drying to obtain modified cellulose; S4, dissolving the modified cellulose prepared in step S3 in DMAC, preparing HAuCl4 solution and dropping it into the reaction system, stirring and reacting for 30-40 minutes, adding NaBH4 aqueous solution to ice water, continuing to stir and react for 15-25 minutes, washing with deionized water, and vacuum drying to obtain a nano detection material.

2. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 1, characterized in that: In step S1, the mass fraction of the cellulose in the methanol aqueous solution is 3%-5%; the mass ratio of AIBN to cellulose is 1:8-10.

3. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 2, characterized in that: In step S2, the mass concentration of the N-hydroxyethyl acrylamide in dichloromethane is 40-50 g / L; the mass ratio of the N-hydroxyethyl acrylamide to methyl imidazole-2-carboxylate is 1:1.1-1.

2.

4. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 3, characterized in that: In step S2, the added mass of the p-toluenesulfonic acid is 10%-12% of the mass of N-hydroxyethyl acrylamide.

5. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 4, characterized in that: In step S3, the imidazolyl acrylamide solution is a solution of imidazolyl acrylamide dissolved in a methanol aqueous solution, wherein the mass concentration of imidazolyl acrylamide is 40-80 g / L, and the volume fraction of methanol in the methanol aqueous solution is 60%-80%.

6. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 5, characterized in that: In step S3, the mass ratio of the imidazolyl acrylamide to the cellulose is 1:1.25-1.5; the added mass of the N,N'-bis(acryloyl)cystamine is 10%-20% of the mass of the imidazolyl acrylamide.

7. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 6, characterized in that: In step S4, the mass fraction of the modified cellulose in DMAC is 1%-4%.

8. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 7, characterized in that: In step S4, in the HAuCl4 solution, the mass concentration of HAuCl4 in DMAC is 4-5 g / L; the added mass of HAuCl4 is 3.6%-5% of the mass of modified cellulose.

9. The method for preparing a nanometer detection material for detecting heavy metal ions in industrial wastewater according to claim 8, characterized in that: In step S4, the mass concentration of NaBH4 in the NaBH4 solution is 10-12 g / L; the added mass of NaBH4 is 4%-6% of the mass of the modified cellulose.

10. A nanometer detection material for detecting heavy metal ions in industrial wastewater, characterized by: The preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing chitosan nanocellulose-base composite spherical adsorption material

    CN106268679A

  • Preparation method for gold nanoparticles modified by polymer polyacrylamide and applications

    CN108844909A

  • Treatment material for heavy metals in sewage and preparation method thereof

    CN111389380A

  • Fluorescent Au NCs ZIF-8 cellulose paper base as well as preparation method and application thereof

    CN116426272A

  • Biological carbon composite sewage treatment agent and preparation method thereof

    CN117819630A